Global climate change increases risk of crop yield losses and food insecurity in the tropical Andes. (15th November 2017) - Tito, Richard; Vasconcelos, Heraldo L.; Feeley, Kenneth J.
Abstract: One of the greatest current challenges to human society is ensuring adequate food production and security for a rapidly growing population under changing climatic conditions. Climate change, and specifically rising temperatures, will alter the suitability of areas for specific crops and cultivation systems. In order to maintain yields, farmers may be forced to change cultivation practices, the timing of cultivation, or even the type of crops grown. Alternatively, farmers can change the location where crops are cultivated (e.g., to higher elevations) to track suitable climates (in which case the plants will have to grow in different soils), as cultivated plants will otherwise have to tolerate warmer temperatures and possibly face novel enemies. We simulated these two last possible scenarios (for temperature increases of 1.3°C and 2.6°C) in the Peruvian Andes through a field experiment in which several traditionally grown varieties of potato and maize were planted at different elevations (and thus temperatures) using either the local soil or soil translocated from higher elevations. Maize production declined by 21%–29% in response to new soil conditions. The production of maize and potatoes declined by >87% when plants were grown under warmer temperatures, mainly as a result of the greater incidence of novel pests. Crop quality and value also declined under simulated migration and warming scenarios. We estimated that local farmers may experience severe economic losses of up to 2, 300 US ha −1 yr −1 . These findings reveal that climate change is a real and imminent threat to agriculture and that there is a pressing need to develop effective management strategies to reduce yield losses and prevent food insecurity. Importantly, such strategies should take into account the influences of non‐climatic and/or biotic factors (e.g., novel pests) on plant development. Abstract : Using a series of field experiments performed in the remote Peruvian Andes, we show that the dangers of climate change for crops include not only the direct effects of rising temperatures but also the indirect effects of changing biotic conditions. Our findings reveal that climate change is a real and imminent threat to agriculture.